Beneath the surface: Application of transparent super absorbent polymer substrates to track faunal activity within the sediment layer. (10th July 2020) - Mathers, Kate L.; Michalec, François‐Gaël; Holzner, Markus; Weber, Christine
Abstract: Tracking the movement of organisms is a fundamental goal of many ecological studies. Several techniques exist in the study of terrestrial and aquatic fauna; however, to date, the ability to monitor aquatic fauna within the sediment layer efficiently and in multiple dimensions is lacking. Given the importance of subsurface sediments in supporting ecosystem functioning, this inability to observe organism behaviour represents a fundamental gap in our knowledge and limits our capability to holistically characterise the response of freshwater systems to stressors. Here we present an experimental study that employs novel transparent super absorbent polymer substrates ( c . 8–12 mm in diameter) in combination with computer vision technology, which enables, for the first time, real‐time observation and tracking of organisms within the sediment layer under lotic flow conditions. Use of these substrates allowed the successful extraction of organism trajectories, which enabled the velocity and body orientation of a freshwater amphipod ( Gammarus fossarum ) in the sediment layer to be calculated in response to a number of vertical hydrological exchange treatments (upwelling, downwelling, and no vertical exchange). Results indicate that under vertical hydrological exchange, a higher proportion of fast velocities (both horizontal and vertical) were recorded for G. fossarum in the sediment layer compared to no vertical exchange (control) conditions. This increase was most marked for upwelling flow exchange. We also observed a change in the body orientation of individuals in the sediment layer from a vertical alignment under no vertical exchange to a more horizontal one under downwelling and more notably upwelling flow exchange. This shift in body position was exacerbated under stronger vertical exchange rates. We identified that following the flow transition of downwelling to upwelling conditions, there was an immediate shift (0–2 min) in both the orientation angle and activity level of individuals. This increased rate of activity was maintained for the individuals' velocity but not for their changing orientation angle. These trends were not apparent within the flow transition of no vertical exchange to downwelling flow. Our new methodological approach enables vital insights into the behaviour of organisms within the sediment layer. Use of super absorbent polymer substrates allows real‐time multi‐directional tracking of multiple organisms in parallel. We believe the method represents an innovative tool that can be employed to tackle a wide range of ecological questions and thereby improve our mechanistic understanding of ecological responses to biotic and abiotic processes/stressors.